THE POSITION OF COLLECTIONS OF SHARIA LAW IN REGULATING KYRGYZ SOCIETY IN THE LATE 19TH AND EARLY 20TH CENTURIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the emergence of Sharia religious law in the public life of 19th-century Kyrgyz in the regulation of public relations. At the threshold of the nineteenth century, the spread of Islam in Kyrgyz public life intensified under the influence of the Kokond Khanate.In par- ticular, in comparison with the tribes of the northern Kyrgyz, the tribes of the southern Kyrgyz have developed a traditional Islamic consciousness through the combination of customary law and Sharita laws. The 19th century is called the era of transition from customary law to sharia in the tribes of the southern Kyrgyz. The sources of Sharia religious law will be analyzed, the working procedure of the judicial system and the powers to regulate society will be considered. Kaziyev’s courts are limited by the responsibilities of judicial analysis and legal law, but they study the functions of analyzing reli- gion, spreading religious facts to society and communicating religious facts to society.
Keywords: : sharia law, Qazi court, kun ransom, diya ransom, flight power, dathi power, customary law.